A study on displaced identity of the trafficked children in the three selected young adult novels of the 21st century - Alobeytha, Faisal Lafee Etan (2018)
Child trafficking is a social disease where its preys endure chronic trauma in which they usually suffer from physical and psychological abuse as well as death. Despite the substantial number of studies on human trafficking available on bookshelves, there is no exact literary study that has tackled the issue of child trafficking separately from human trafficking. This research aims to study the ecological environment that contributes to the continuous emergence of child trafficking. It also examines the effects of ecological environment on the identity of the children in three selected novels: Uzodinma Iweala's Beast of No Nation, Patricia McCormick's Sold and Kashmira Sheth's Boys without Names. Bronfenbrenner’s Ecological System Theory (EST) was used as a theoretical framework for this study. A thematic approach by Braun and Clarke (2006) was used to analyse these literary texts. The overall findings of this study show that (i)traffickers always aim to erase the identity of the trafficked children and replace it with the identity of slaves; (ii) ecological structures have contributed to the identity development of these trafficked children; (iii) by recalling the history of the trafficked children, they may recover their identities and resist the traffickers. This study encourages scholars to extend their investigations to include novels which were published after 2010. It also suggests that there is a need to study the identity and self-esteem of traffickers. Future research is necessary to improve and elaborate on the new findings. It is important to focus on more new topics on child trafficking such as child organ trafficking, child drug trafficking and child begging trafficking in Young Adult Literature or other sorts of literature. It is necessary to study the identities of the survivals.